Foods for special needs - Harding, Ben; Video Educational Australasia (Australia : Video Educational Australasia, 2005)
Examines food allergies and intolerances, dietary-related diseases and disorders. Cultural and religious belief that determine diet also considered
Title from title screen
Executive producer, Mark McAuliffe ; sound, Wayne Martin ; editor/graphics, Paul Sutherland
Voice over: Mark Collard
Keywords: Food service; Food service management; Dietetics